Petrographic and geochemical studies of the alteration zones associated with gold mineralization at the Holloway mine, southwestern Abitibi Greenstone Belt, Canada. - Ropchan, Jean Claudia. (University of Ottawa (Canada), 2000)
The Holloway mine is an Archean lode gold deposit hosted within the southwestern Abitibi greenstone belt. Rocks hosting the deposit are bounded by two main branches of the Destor Porcupine fault zone and belong to the Destor Porcupine Complex. Meta-volcanic rocks of the Destor Porcupine Complex were tested using the Treuil method and shown to belong to a tholeiitic suite that differentiated via fractional crystallization producing three distinct groups: tholeiitic meta-basalts, Fe-tholeiitic meta-volcanic rocks, and variolitic meta-volcanic rocks. Alteration at the Holloway deposit consists of a silicified and albitized core surrounded by halos of sericite and carbonate alteration. Carbonate alteration is composed mainly of ankerite and appears pervasive due to many overlapping hydrothermal events. Lightning Zone mineralization is the earlier of two gold mineralizing events. It is associated with finegrained disseminated pyrite and hosted by silicified and albitized variolitic meta-volcanic rocks having variolitic and hyaloclastite textures. Results from statistical factor analysis show that gold-bearing hydrothermal fluids contain S, W, and sometimes As. Both episodes of gold mineralization only occur within meta-volcanic rocks that have a Fe/Mg = 8. (Abstract shortened by UMI.)
Keywords: Geochemistry.